The Relationship between Serum Zinc and Glycemic Control among Type 2 Diabetic Patients in Khartoum State, Sudan - Rahmtalla, Suzan A.; Modawe, Gad Allah; Abdalla, Abdelmula M.; Gurashi, Rimaz; Hamad, Shereen F.; Rahmtalla, Suhair A (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Previous studies suggest a significant relationship between type 2 diabetes mellitus (T2DM) and a lack of zinc. A lack of zinc can negatively impact insulin synthesis, storage, and secretion, leading to insulin resistance and inadequate glycaemic control. Nevertheless, the correlation between serum zinc levels and glycaemic control in T2DM has not been well studied in various populations. Objective: To investigate the relationship between serum zinc levels and glycaemic control, assessed by HbA1c, in individuals diagnosed with type 2 diabetes mellitus. Methods: This case-control study was carried out between April 2018 and July 2019 at Omdurman Teaching Hospital in Khartoum State, Sudan. The study included 100 participants: 50 were T2DM patients, and the other 50 were healthy individuals who served as controls. Serum zinc levels were determined with atomic absorption spectrophotometry, while HbA1c levels were evaluated with the Ichroma system. Data analysis was performed using SPSS, version 25. A comparative analysis was conducted on the groups, with correlation coefficients being calculated to investigate the correlations between age, serum zinc, and HbA1c levels. Results: The diabetics showed notably lower zinc levels in their blood compared to the control group, along with notably elevated HbA1c levels. In diabetic individuals, age correlated positively with HbA1c and serum zinc levels. Additionally, diabetic patients showed a significant inverse correlation between their serum zinc levels and HbA1c values. Conclusion: This research indicates that individuals with diabetes might exhibit decreased zinc levels in their bloodstream and that a connection could exist between age, zinc levels in the bloodstream, and HbA1c levels in these individuals. The results of this research may impact how diabetes mellitus and zinc deficiency are managed.